2021
DOI: 10.3390/ma14175087
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Band Conformal Antenna Based on Highly Conductive Graphene-Assembled Films for 5G WLAN Applications

Abstract: Flexible electronic devices are widely used in the Internet of Things, smart home and wearable devices, especially in carriers with irregular curved surfaces. Light weight, flexible and corrosion-resistant carbon-based materials have been extensively investigated in RF electronics. However, the insufficient electrical conductivity limits their further application. In this work, a flexible and low-profile dual-band Vivaldi antenna based on highly conductive graphene-assembled films (GAF) is proposed for 5G Wi-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The proposed antenna is configured by a coplanar waveguide line to feed the antenna with a characteristic impedance Z 0 . In addition, the antenna has two radiator patches with an isosceles trapezoidal form [ 30 , 31 , 32 , 33 ]; Figure 1 shows the geometry of the proposed antenna. In this geometry, w 4 controls the lowest frequency band ( f min ), and w 2 works over the higher frequency band ( f min ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed antenna is configured by a coplanar waveguide line to feed the antenna with a characteristic impedance Z 0 . In addition, the antenna has two radiator patches with an isosceles trapezoidal form [ 30 , 31 , 32 , 33 ]; Figure 1 shows the geometry of the proposed antenna. In this geometry, w 4 controls the lowest frequency band ( f min ), and w 2 works over the higher frequency band ( f min ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, taking advantage of the flexibility of graphene, Zelong et al [ 31 ] reported a dual-band flexible antenna using a graphene film over a polydimethylsiloxane substrate. Finally, it is essential to mention that designs of graphene antennas over glass as a substrate barely exist.…”
Section: Introductionmentioning
confidence: 99%
“…A dual-band wearable conformal antenna realized with highly conductive graphene film was reported in [64]. The operating frequency of the flexible GAF antenna covered the Wi-Fi band, 2.4-2.45 GHz and 5.15-7.1 GHz.…”
Section: H Graphene Filmmentioning
confidence: 99%
“…[26][27][28][29] In addition, as a carbon material, graphene has better chemical stability and adaptability to harsh environments than its metal counterparts. 30 Due to the excellent flexibility of graphene, it has been used in various wearable antennas such as pressure sensor, 31 ultra-wideband antenna, 32 nearfield communication (NFC) tag antenna, 33 dual-band conformal antenna, 34 and millimeter wave antenna array, 35 which proves that graphene can be used in flexible devices.…”
Section: Introductionmentioning
confidence: 99%